Situation Report: Romania, 2 December 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Long-Term Economic Agreement Signed with US Visits of Expatriate Romanians Facilitated Material and Product Allocation and Contracting Remain Unsatisfactory Inefficiency and Reorganization in Metallurgy New First Deputy Minister of the Interior Appointed CC Plenum Decision on Implementation of the Ideological Action Program Severe Criticism of Romanian Physical Education and Sports